ReIU: an efficient preliminary framework for Alzheimer patients based on multi-model data - Jiang, Hao; Qian, Yishan; Zhang, Liqiang; Jiang, Tao; Tai, Yonghang (Frontiers in Public Health, 2025)
The rising incidence of Alzheimer’s disease (AD) poses significant challenges to traditional diagnostic methods, which primarily rely on neuropsychological assessments and brain MRIs. The advent of deep learning in medical diagnosis opens new possibilities for early AD detection. In this study, we introduce retinal vessel segmentation methods based on U-Net ad iterative registration Learning (ReIU), which extract retinal vessel maps from OCT angiography (OCT-A) facilities. Our method achieved segmentation accuracies of 79.1% on the DRIVE dataset, 68.3% on the HRF dataset. Utilizing a multimodal dataset comprising both healthy and AD subjects, ReIU extracted vascular density from fundus images, facilitating primary AD screening with a classification accuracy of 79%. These results demonstrate ReIU’s substantial accuracy and its potential as an economical, non-invasive screening tool for Alzheimer’s disease. This study underscores the importance of integrating multi-modal data and deep learning techniques in advancing the early detection and management of Alzheimer’s disease.